Barriers and financial impact of same‐day discharge after atrial fibrillation ablation. Issue 4 (15th March 2021) - Chu, Edward; Zhang, Chi; Musikantow, Daniel R.; Turagam, Mohit K.; Langan, Noelle; Sofi, Aamir; Choudry, Subbarao; Syros, Georgios; Miller, Marc A.; Koruth, Jacob S.; Whang, William; Dukkipati, Srinivas R.; et al.
Abstract: Background: Same‐day discharge (SDD) after atrial fibrillation (AF) ablation is increasingly being considered. This study examined the barriers and financial impact associated with SDD in a contemporary cohort of patients undergoing elective AF ablation. Methods: A single center retrospective review was conducted of the 249 first case‐of‐the‐day outpatient AF ablations performed in 2019 to evaluate the proportion of patients that could have undergone SDD. Barriers to SDD were defined as any intervention that prevented SDD by 8 p.m. The financial impact of SDD was based on savings from avoidance of the overnight hospital stay and revenue related to management of chest pain facilitated by a vacant hospital bed. Results: SDD could have occurred in 157 patients (63%) without change in management and in up to 200 patients (80%) if avoidable barriers were addressed. Barriers to SDD included non‐clinical logistical issues (43%), prolonged post‐procedure recovery (42%) and minor procedural complications (15%). On multivariate analysis, factors associated with barriers to SDD included increasing age ( P = .01), left ventricular ejection fraction ≤ 35% ( P = .04), and severely dilated left atrium ( P = .04). The financial gain from SDD would have ranged from 1, 110, 096 (assuming discharge of 63% of eligible patients) to 1, 480, 128 (assuming 80% discharge) over the course of a year. Conclusions: Up to 80% of patients undergoing outpatient AF ablation were amenable to SDD if avoidable delays in care had been anticipated. Based on reduced hospital operating expenses and increased revenue from management of individuals with chest pain, this would translate to a financial savings of ∼1.5 million.